Accounting for magnetic saturation in induction machines modelling. (1st January 2011) - Ouadi, Hamid; Giri, Fouad; Dugard, Luc
A new model is developed for (uniform air-gap) induction motor that accounts for the saturation feature of the machine magnetic circuit. It is built-up starting from the basic electrical/mechanical laws and turns out to be quite different from the standard model that is widely used in control oriented literature. Specifically, the new model involves state-dependent parameters. An experimental validation using a real 7.5 kW machine proved the good accuracy of the proposed model.